The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.cub.2012.11.046
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NEDD1 Phosphorylation by Aurora A in Chromosomal Microtubule Nucleation and Spindle Function

Abstract: Chromatin directs de novo microtubule (MT) nucleation in dividing cells by generating a gradient of GTP-bound Ran protein (RanGTP) that controls the activity of a number of spindle assembly factors (SAFs). It is now well established that these MTs are essential for the assembly of a functional bipolar spindle. Although it has been shown that RanGTP-dependent MT nucleation requires γ-tubulin and a number of RanGTP-regulated proteins, the mechanism involved is still poorly understood. We previously showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…Consistent with this notion, the regulatory factors NEDD1 and CDK5RAP2 have a significantly higher turnover rate compared to the γTuRC structural core subunits γ-tubulin, GCP2, GCP3, GCP4, GCP5 and GCP6 (Jakobsen et al, 2011). Moreover, NEDD1 is phosphorylated at multiple sites to specifically control γTuRC function in distinct mitotic nucleation pathways (Gomez-Ferreria et al, 2012;Haren et al, 2009;Johmura et al, 2011;Lüders et al, 2006;Pinyol et al, 2013;Scrofani et al, 2015;Sdelci et al, 2012;Teixidó-Travesa et al, 2010. Future work will show whether human MZT1 is subject to similar regulation.…”
Section: Discussionsupporting
confidence: 58%
“…Consistent with this notion, the regulatory factors NEDD1 and CDK5RAP2 have a significantly higher turnover rate compared to the γTuRC structural core subunits γ-tubulin, GCP2, GCP3, GCP4, GCP5 and GCP6 (Jakobsen et al, 2011). Moreover, NEDD1 is phosphorylated at multiple sites to specifically control γTuRC function in distinct mitotic nucleation pathways (Gomez-Ferreria et al, 2012;Haren et al, 2009;Johmura et al, 2011;Lüders et al, 2006;Pinyol et al, 2013;Scrofani et al, 2015;Sdelci et al, 2012;Teixidó-Travesa et al, 2010. Future work will show whether human MZT1 is subject to similar regulation.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, AurA has been shown to be required for MT nucleation/stabilization through the RanGTP-dependent pathway in the early phases of mitosis [4,8,18]. We have shown here that AurA kinase activity is required during anaphase for central spindle assembly.…”
Section: Scientific Reportmentioning
confidence: 66%
“…AurA is required for mitotic entry, centrosome maturation and separation and for bipolar spindle formation [3]. Further insights into AurA function have been obtained through the identification of some of its substrates [3][4][5]. One of its best characterized substrate is TACC3, a protein that promotes MT stabilization through its interaction with chTOG/XMAP215 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with this notion, it was shown that NEDD1 is phosphorylated by AurA and Plk1 (Haren et al, 2009; Pinyol et al, 2013; Zhang et al, 2009) and that its phosphorylation status depends on Cep192 in mammalian cells (Gomez-Ferreria et al, 2012). …”
Section: Discussionmentioning
confidence: 80%